The Holy Land on the Florentine Confraternity Stage - Eisenbichler, Konrad (Confraternitas, 2022)
This article examines how Italian dramatists of the fifteenth and sixteenth centuries represented the Holy Land in the plays that they composed for performance by young men in religious confraternities. The fact that these plays were meant to have a strong pedagogical purpose makes their representation of the Holy Land all the more important not only for the historical aspect of how ancient Palestine was understood and represented in early modern Italy, but also for what this representation meant for Christians and Jews living in early modern Italy. The questions of historical understanding and knowledge are thus closely tied to the questions of the revival of interest in Hebraic knowledge in Renaissance Italy and of the growing anti-Semitism of the time (when ghettos were established in cities such as Venice and Florence, to mention just two). At the same time, when a city such as Florence begins to envision itself and present itself as “the new Jerusalem,” the depiction of Jerusalem (in particular) and the Holy Land (in general) in the religious plays mounted by its young men becomes all the more revealing. The Holy Land can thus be both the exotic Orient and quotidian Florence, part of the East and of the West, both Hebrew and Christian. By extension, the “Jew” can be the “Other” but also the “Self.”